(untitled) (Journal of the College of Basic Education, 2022)
The study aimed at identifying the gradient and the ratio of the contribution and forecasting defensive movements of short-term (front. Background. profiles) in terms of the numerical values of some of the physiological indicators (time of the emergence of distinguishing threshold anaerobic treatment (Anaerobic Threshold), the average number of heart strikes during the voltage (HR-Bpm), the pinnacle of the oxygen during effort,FeO2) to young players for handball, the researcher used the descriptive approach Coalition style of the type of linear, on a sample of young players in the Clubs of Baghdad(2016) for handball of (25), the player of selected random way, after identifying the variables and specifications of tests and the exploratory experience was the holding of the application of the master craftsman test for handball under discussion, mayors, a researcher of the adoption of modern technologies in the laboratories of the physiology of sport measuring both physiological indicators (time of the emergence of distinguishing threshold anaerobic treatment, pulse rate during The effort, the pinnacle of the oxygen during the voltage) in the fitness room, and a football pitch to hand in the Faculty of Physical Education and Sports Sciences, University of Baghdad, and was addressing the statistical results the use of program (SPSS) version (V24), then the researcher reached the following conclusions: the adoption of the linear and the rate of contribution of each time the emergence of distinguishing threshold anaerobic treatment, pulse rate during the effort, the pinnacle of the oxygen during the voltage) predictable digital values defensive moves short-term (front. Background. profiles) to young players for handball.